Model Komunikasi Guru Dalam Membentuk Karakter Siswa Madrasah Diniyyah Haji Ya’qub Lirboyo Kediri - Agus Saifudin; Tri Prasetiyo Utomo; Marita Lailia Rahma (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to describe the teacher communication model in shaping students’ character at Madrasah Diniyyah Haji Ya’qub, Kediri City. The research employs a qualitative field approach with a descriptive-analytical design. Data were collected through interviews, observations, and documentation, then analyzed using a flow model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the teacher’s communication process begins with verbal communication, reinforced by nonverbal interactions and the supportive school environment. Teachers apply the Berlo communication model and the stimulus–response model through persuasive and spiritual approaches in the learning process. The effectiveness of character formation is influenced by three main factors: the teacher’s communication model, the educational environment, and spiritual development pathways, all of which are harmoniously integrated into the teaching and learning activities.